16-year WRF simulation for the Southern Alps of New Zealand - Kropac, Elena; Mölg, Thomas; Cullen, Nicolas James (2023)
The climatological dataset was produced using the Weather and Research Forecasting (WRF) model, version 4.2.2, configured with two nested domains at 10 km (D1) and 2 km (D2) horizontal grid spacing. It covers most of the South Island of New Zealand and is centered over Brewster Glacier in the Southern Alps. The model was forced every three hours by ERA5 reanalysis data at its outer lateral boundaries. The dataset spans the period of 1 January 2005 to 31 December 2020, providing daily output in the outer domain (D1) and 3-hourly output in the innermost domain (D2). The data provided here are a selection of daily averages from the inner WRF domain (D2; 2-km grid spacing). They are distributed among three different file types containing 4-dimensional, 3-dimensional and time-invariant output variables, respectively. For the 4-dimensional fields, perturbation and base-state atmospheric pressure (WRF variables P and PB) and geopotential (PH and PHB) were combined to produce full model fields (PRES and GEOPT). Perturbation potential temperature (T) was converted to total potential temperature (THETA). Wind vectors (U,V, and W) were converted to mass points and rotated to earth coordinates.<br

A Detailed, Multi-Scale Assessment of an Atmospheric River Event and Its Impact on Extreme Glacier Melt in the Southern Alps of New Zealand - Kropac, Elena; Mölg, Thomas; Cullen, Nicolas J.; Collier, Emily; Pickler, Carolyne; Turton, Jenny (Journal of Geophysical Research: Atmospheres, 2021)
North-westerly airflow and associated atmospheric rivers (ARs) have been found to profoundly influence New Zealand’s west coasts, by causing flooding, landslides and extreme ablation and accumulation on glaciers in the Southern Alps. However, the response of local glacier mass balance to synoptic-scale circulation, including events with ARs, has typically not been investigated by considering mesoscale processes explicitly. In this study, high-resolution atmospheric simulations from the Weather Research and Forecasting model are used to investigate the mesoscale drivers of an extreme ablation event on Brewster Glacier (Southern Alps), which occurred on February 6, 2011 during the landfall of an AR on the South Island. The following processes were found to be crucial for transferring the high temperature and water vapor contained in the AR into energy available for melt on Brewster Glacier: First, the moist-neutral character of the air mass enabled the flow to pass over the ridge, leading to the development of orographic clouds and precipitation on the windward side of the orography, and foehn winds on the leeside. These processes fueled melt through longwave radiation and strong turbulent and rain heat fluxes within the high-condensation environment of the orographic cloud. Second, orographic enhancement occurred due to both cellular convection within the cloud and the combined effect of multiple precipitating systems by the seeder-feeder-mechanism. These results indicate the potential importance of AR dynamics for New Zealand’s glaciers. They also illustrate the benefit of mesoscale atmospheric modeling for advancing process understanding of the glacier-climate relationship in New Zealand.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Atmospheric river; glacier ablation; mesoscale processes; New Zealand Southern Alps; orographic precipitation; WRF

A new, high-resolution atmospheric dataset for southern New Zealand, 2005–2020 - Kropac, Elena; Mölg, Thomas; Cullen, Nicolas J. (Geoscience Data Journal, 2024)
The regional climate of New Zealand's South Island is shaped by the interaction of the Southern Hemisphere westerlies with the complex orography of the Southern Alps. Due to its isolated geographical setting in the south-west Pacific, the influence of the surrounding oceans on the atmospheric circulation is strong. Therefore, variations in sea surface temperature (SST) impact various spatial and temporal scales and are statistically detectable down to temperature anomalies and glacier mass changes in the high mountains of the Southern Alps. To enable future studies on the processes that govern the link between large-scale SST and local-scale high-mountain climate, we utilized dynamical downscaling with the Weather Research and Forecasting (WRF) model to produce a regional atmospheric modelling dataset for the South Island of New Zealand over a 16-year period between 2005 and 2020. The 2 km horizontal resolution ensures realistic representation of high-mountain topography and glaciers, as well as explicit simulation of convection. The dataset is extensively evaluated against observations, including weather station and satellite data, on both regional (in the inner domain) and local (on Brewster Glacier in the Southern Alps) scales. Variability in both atmospheric water content and near-surface meteorological conditions is well captured, with minor seasonal and spatial biases. The local high-mountain climate at Brewster Glacier, where land use and topographic model settings have been optimized, yields remarkable accuracy on both monthly and daily time scales. The data provide a valuable resource to researchers from various disciplines studying the local and regional impacts of climate variability on society, economies and ecosystems in New Zealand. The model output from the highest resolution model domain is available for download in daily temporal resolution from a public repository at the German Climate Computation Center (DKRZ) in Hamburg, Germany (Kropač et al., 2023; 16-year WRF simulation for the Southern Alps of New Zealand, World Data Center for Climate (WDCC) at DKRZ [data set]. https://doi.org/10.26050/WDCC/NZ-PROXY_16yrWRF).
CRIS-Team Scopus Importer:2024-07-12
Keywords: climate data; downscaling; high-mountain climate; southern hemisphere; WRF model

A new, high-resolution climatological atmospheric dataset for southern New Zealand - Kropac, Elena; Mölg, Thomas; Cullen, Nicolas James (EGU General Assembly 2023, 2023)
The regional climate of New Zealand’s South Island is shaped by the interaction of the Southern Hemisphere westerlies with the complex orography of the Southern Alps. Due to the geographical setting of New Zealand in the south-west Pacific, the properties of the transported air masses and the regional circulation itself are strongly influenced by the surrounding oceans. Therefore, variations in sea surface temperature (SST) are reflected on a variety of spatial and temporal scales and are statistically detectable through to temperature anomalies and glacier mass balance changes in the high mountains of the Southern Alps. The relationship between SST and high-mountain climate has not yet been investigated from a process perspective, leaving the underlying physical mechanisms that transmit large-scale SST signals to local climate anomalies and glacier mass changes unknown. We used dynamical downscaling with the Weather Research and Forecasting (WRF) model laterally forced by ERA5 reanalysis data to produce a regional atmospheric modeling dataset for the South Island of New Zealand. The dataset covers the present-day, 16-year period of 2005 to 2020. The high horizontal resolution of 2 km ensures that high-mountain topography and glaciers are resolved realistically, and convection is modeled explicitly. The two-domain setup is centered on Brewster Glacier, a benchmark glacier close to the main divide of the Southern Alps, which is the focus of further process-oriented investigations. The model configuration has been optimized to provide both reasonable output and fast simulation time, allowing for expense-limited follow-up sensitivity experiments. The dataset is evaluated regionally against an extensive network of observational meteorological data from the National Institute of Water and Atmospheric Research (NIWA) and MetService New Zealand as well as against atmospheric water content from Moderate Resolution Imaging Spectroradiometer (MODIS) imagery. Locally, the model output is compared to high-mountain weather station measurements at Brewster Glacier. The model represents variability in both atmospheric water content and near-surface meteorological conditions generally well, although there are both seasonal and spatial biases that are particularly confined to high elevations. The local climate at Brewster Glacier (where landuse and topographic conditions have been optimized) is remarkably well represented on both seasonal and daily timescales. Given the fact that the Southern Hemisphere has been understudied in terms of multiscale climate and cryosphere relations, the dataset provides a unique and valuable tool for investigations of climate change and related impacts in southern New Zealand with high interdisciplinary relevance. Data from the finest-resolution model domain are available for download at daily temporal resolution from a public repositor

Das Potenzial coralliner Rotalgen als SST-Proxy und für die Evaluierung globaler Klimamodelle: eine Fallstudie in Neuseeland - Kropac, Elena; Mölg, Thomas; Teichert, Sebastian (Tagungsband zur 39. Sitzung des Arbeitskreises Klima, 2021)
Globale Klimamodelle (General Circulation Models; GCMs) sind das aktuell wichtigste Instrument der Klimawissenschaft, um Aussagen und Projektionen über das Klima der Zukunft zu treffen. Sie liefern zudem Daten-Input für regionale Atmosphärenmodelle, mithilfe derer der sog. „Klima-Impakt“ großräumiger Klimaänderungen auf regionaler und lokaler Ebene berechnet werden kann. Um möglichst akkurate Projektionen und Inputdaten zu gewährleisten, müssen GCMs bestmöglich mit Klimaaufzeichnungen der Vergangenheit evaluiert werden, wobei der Fokus auf der sog. "historischen Periode" von 1850 bis zur Gegenwart liegt. Die Evaluierung ist für den Zeitraum vor 1950, und insbesondere für die Südliche Hemisphäre, aufgrund der stark eingeschränkten Verfügbarkeit und Qualität von Beobachtungsdaten jedoch schwierig. Im Rahmen des im Februar 2021 angelaufenen Projekts „NZ-PROXY“ werden krustenbildende coralline Rotalgen (KCA) als Klimaindikatoren eingesetzt, um – analog zu dendrochronologischen Rekonstruktionen der terrestrischen Lufttemperatur – die Beobachtungszeitreihe der Meeresoberflächentemperatur (SST) in Neuseeland bis 1850 zu verlängern. KCA zeichnen sich im Vergleich zu anderen marinen Klima-Indikatoren u.a. durch ihre weltweite Verbreitung, zeitlich hochaufgelöste Information und relativ leichte Zugänglichkeit aus. Der mithilfe der KCA neu gewonnene, historische SSTDatensatz soll für die Evaluierung von GCMs in der Neuseelandregion verwendet werden und somit die Auswahl geeigneter GCM-Inputdatensätze für regionale Atmosphärenmodelle und die Verbesserung regionaler Klimamodellierung ermöglichen. Aufgrund seiner einzigartigen geographischen Lage ist Neuseeland von ozeanischer und atmosphärischer Klimavariabilität gleichermaßen beeinflusst; Variationen der SST schlagen sich dort auf einer Vielzahl von räumlichen und zeitlichen Skalen nieder und sind bis hin zu Temperaturanomalien und Gletschermassenbilanzänderungen im Hochgebirge der Südlichen Alpen statistisch detektierbar. Eine korrekte Simulation der SST durch GCMs ist daher essentiell und kann im Rahmen der regionalen Modellierung dazu beitragen, die physikalischen Mechanismen zu entschlüsseln, die großräumige SST-Signale in lokale Klimaanomalien umwandeln. Im Vortrag werden der Forschungsansatz sowie erste Ergebnisse aus Laboranalysen und Modellierungen vorgestellt. <br

Mesoscale atmospheric circulation controls of local meteorological elevation gradients on Kersten Glacier near Kilimanjaro summit - Mölg, Thomas; R. Hardy, Douglas; Collier, Emily; Kropac, Elena; Schmid, Christina; J. Cullen, Nicolas; Kaser, Georg; Prinz, Rainer; Winkler, Michael (Earth System Dynamics, 2020)
Elevation gradients of meteorological variables in mountains are of interest to a number of scientific disciplines and often required as parameters in modeling frameworks. Measurements of such gradients on glaciers, however, are particularly scarce and strongly skewed towards the midlatitudes and valley glaciers. This article adds a tropical perspective and presents 4 years of overlapping measurements at 5603 and 5873m on Kersten Glacier, Kilimanjaro (East Africa), between 2009 and 2013. Mean gradients in near-surface air temperature (T ), water vapor pressure (VP), and snow accumulation (ACC) per 100m elevation are 0:75 C, 0:16 hPa, and 11416mmw.e. yr1, respectively. An intriguing feature is a strong diurnal cycle of the T and VP gradients, which are (depending on season) 2-4 times larger between early and late morning than in the hours of weak gradients. The ACC decrease with elevation, furthermore, is mostly the result of a lower recorded frequency of ACC events at the upper measurement site and not due to contrasting amounts at the two altitudes during events. A novel facet of our study is the linking of measured on-glacier gradients to a high-resolution atmospheric modeling data set, which reveals the importance of the mesoscale atmospheric circulation. A thermally direct circulation is established over the mountain in response to diabatic surface heating or cooling with upslope flow during the day and downslope flow in the night. This persistent circulation communicates heat and moisture changes in the lowlands to the higher elevations during morning and early afternoon, which is evident in the advection patterns of potential temperature and VP, and shapes the time variability in gradients as recorded by our weather stations on the glacier. A few local processes seem to matter as well (glacier sublimation, turbulent heat fluxes), yet they show a secondary influence only during limited time windows. Atmospheric model data also demonstrate that declining moist entropy and water vapor fluxes in the summit zone favor formation of the negative ACC gradient. The results extend the empirical basis of elevation gradients in high mountains, in particular over glacier surfaces, by the unusual case of a slope glacier on an equatorial, free-standing massif. Our measurement-model link, moreover, demonstrates an approach for future studies to put observations of elevation gradients more systematically in a multiscale process context.
CRIS-Team Scopus Importer:2020-08-21

The potential of coralline algae as SST proxy and for climate model evaluation: A New Zealand case study - Kropac, Elena; Mölg, Thomas; Teichert, Sebastian (EGU General Assembly 2022, 2022)
General circulation models (GCMs) are currently the most important tools for obtaining projections about future climate. In addition, they provide data input for regional atmospheric models that translate global climate change to regional and local scales where humans and environments face the impacts. To ensure the accurateness of their simulations, GCMs need to be evaluated as thoroughly as possible against past climate records, where one focus is on the so-called "historical period" (1850–present). However, the evaluation task is difficult for the period before World War II and earlier due to a frequent lack of reliable observations. This problem is exacerbated for the Southern Hemisphere, which has been notoriously understudied in comparison to the climate of the Northern Hemisphere. In New Zealand, variations in sea surface temperature (SST) are reflected on a variety of spatial and temporal scales and are statistically detectable through to temperature anomalies and glacier mass balance changes in the high mountains of the Southern Alps. The correct simulation of SST by GCMs is therefore crucial, especially when investigating the physical mechanisms that transform large-scale SST signals into local climate anomalies by using regional atmospheric modeling. In the project “NZ-PROXY”, we utilize crustose coralline algae (CCA) – a rather recently discovered proxy archive – to extend the observational time series of SST in the New Zealand region back to 1850. The SST reconstruction is then employed in GCM evaluation to reveal their skill in representing the large-scale climate of New Zealand. Finally, high-resolution sensitivity simulations are obtained from a regional atmospheric model to investigate the added value of the advanced GCM selection for regional climate modelin